Study Biodiversity of Cladocera in the Kuffa River- Iraq - et.al, Muhanned Nashaat Remzi (Al-Qadisiyah Journal of Pure Science, 2017)
This study carry out to know the biodiversity of cladocera in Kuffa River four representative sampling stations were selected in river monthly sampling were collected from March 2012 to February 2013 The results showed the cladocera high density in April 2012.Also The results of relative abundance index showed that these species Alona rectangular, Bosmina longirostris, Chydorus Sphaeriucus, Ceriodaphnia rigaudi, Simocephalus vetulus . were more abundant in study stations The results showed The index values of Species richness varied between (0.9-8.13) Shannon-Weiner index varied between (0.001-3.04) bit/ind while the uniformity index varied between ( 0.01 – 1) .